2019
DOI: 10.18280/ts.360102
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition Using NLPCA and SVM

Abstract: The aim of this present work is to achieve better accuracy of facial emotion recognition and classification with limited training samples under varying illumination. A method (involving two versions) for achieving high accuracy with limited samples is proposed. Global and local features of facial expression images were extracted using Haar Wavelet Transform (HWT) and Gabor wavelets respectively. Dimensionalities of extracted features are reduced using Nonlinear principal component analysis (NLPCA). Concatenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
(13 reference statements)
0
11
0
2
Order By: Relevance
“…The recent approaches in computer vision, especially in the fields of machine learning and deep learning have improved the efficiency of image classification tasks [1][2][3][4][5][6]. Detection of defected fruits and the classification of fresh and rotten fruits represent one of the major challenges in the agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…The recent approaches in computer vision, especially in the fields of machine learning and deep learning have improved the efficiency of image classification tasks [1][2][3][4][5][6]. Detection of defected fruits and the classification of fresh and rotten fruits represent one of the major challenges in the agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Benkaddour and Bounoua [17] conducted feature extracted with deep convolutional neural network (DCNN) and completed face recognition by the PCA and support vector classifier (SVC). Reddy et al [18] suggested recognizing facial emotions with nonlinear principal component analysis (NLPCA) and support vector machine (SVM). All these methods shed new lights on the identification of small samples, and will be referred to in our future research.…”
Section: Discussionmentioning
confidence: 99%
“…For our experiments, the word vector dimension was set as 128, the size of the hidden LSTM layer as 256, the activation function as ReLU, and the minimum batch size of training as 16. A total of 100 kernels were selected from the value range of { (2,3,4), (3,4,5), (4,5,6)}. Adam was chosen as the optimization function, the learning rate was initialized as 0.001, and the cross entropy was defined as the loss function.…”
Section: Hyperparameter Settingsmentioning
confidence: 99%
“…The popular traditional ML methods include naive Bayes [3], decision tree (DT) [4], k-nearest neighbors (k-NN) [5], support vector machine (SVM) [6], etc. These methods usually represent the text as high-dimensional sparse vectors, which requires manual annotation to construct features [7].…”
Section: Introductionmentioning
confidence: 99%